Reactive or Immune: Stock Market Behaviour During Subsequent Waves of the COVID-19 Pandemic - Daruwala, Zaheda (International Journal of Economics and Financial Issues, 2022)
The COVID-19 pandemic, since its onset, has erupted in waves over the past two years. Previous studies investigated the initial impact of the outbreak on stock market returns. This study extends the investigation of the impact on stock market returns during subsequent waves of the pandemic. A panel data regression of stock market returns to covid variables during the three waves indicated that the initial fear of the disease did not persist through the later waves and the fear factor of the disease spread, deaths and lockdowns faded with every subsequent wave. Investors reacted differently to certain COVID variables. The daily count of total cases and daily deaths were the variables of interest for the first wave, whereas, for subsequent waves, the growth in daily new cases was the most prominent. The country-wise analysis over periods of waves of the pandemic revealed that investor behaviours varied among countries with no identifiable pattern indicating the significance of societal behaviours affecting investor decisions, especially during the crises.